Infringement of personality rights via the internet and private international law - Caamiña Domínguez, Celia M. (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article deals with the infringement of personality rights via the Internet. The rules governing jurisdiction under the Regulation (EU) 1215/2012 and the Spanish Law will be analysed, paying special attention to Art. 7 (2) Regulation (EU) 1215/2012. According to the decisions of the Court of Justice of the European Union, the victim has the option of bringing an action for liability before the courts of the Member State in which the centre of his/her interests is based.